2015
DOI: 10.4103/1947-2714.159331
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of morbidity and mortality in organophosphorus poisoning: A case study in rural hospital in Karnataka, India

Abstract: Background:Organophosphorus (OP) pesticides poisoning can result from occupational, accidental or intentional exposure. Clinical manifestations include cholinergic syndromes, central nervous (CNS) system and cardiovascular disorders. Death is usually due to cardiovascular and respiratory failure.Aim:To evaluate various parameters that can predict outcome of patients in OP poisoning.Materials and Methods:A prospective study conducted in Department of Medicine, Adichunchingiri Institute Of medical Sciences and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
29
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 18 publications
12
29
2
Order By: Relevance
“…In the present study the mean age for the patients was 23.4 years and most of patients were belonging to teenager and middle age group (18 -40 years) represent 44.5% of the patients in the study. This finding was in accordance with Ahmed et al (2014) and Banday et al (2015) in which the incidence was highest in patients aged less than 40 years. There were only 2% of all patients included in the study above age of 60 years and this was in agreement with Chintale et al (2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study the mean age for the patients was 23.4 years and most of patients were belonging to teenager and middle age group (18 -40 years) represent 44.5% of the patients in the study. This finding was in accordance with Ahmed et al (2014) and Banday et al (2015) in which the incidence was highest in patients aged less than 40 years. There were only 2% of all patients included in the study above age of 60 years and this was in agreement with Chintale et al (2016).…”
Section: Discussionsupporting
confidence: 93%
“…There were only 2% of all patients included in the study above age of 60 years and this was in agreement with Chintale et al (2016). This could be explained by the vulnerability to various emotional conflicts that can happen during this phase (teenager and middle age groups) of life in which the people are most ambitious and productive (Banday et al, 2015).…”
Section: Discussionsupporting
confidence: 67%
“…This finding is similar to that of the previous studies. [20] The average duration of mechanical ventilation observed in this study is in agreement with observations of the previous studies,[142324] there was no difference in the duration of mechanical ventilation in patients receiving magnesium compared to control. A single dose of MgSO 4 may not be enough to maintain a sustained therapeutic level which may influence the duration of mechanical ventilation.…”
Section: Discussionsupporting
confidence: 92%
“…It is consensus that even among patients receiving intensive care, such as ventilatory support, gastric lavage and standard therapy with the antidotes, atropine and pralidoxime, mortality is still high for these groups of individuals. The mortality rate in intensive care units is around 10-50% even with mechanical ventilation (Banday et al, 2015;Munidasa et al, 2004;Tang et al, 2016). Munidasa et al (2004) reported that the mortality rate among the patients studied was 50%, even with mechanical ventilation and oxygen supplementation.…”
Section: Discussionmentioning
confidence: 95%